Current Research in Ayush (Alternative Medicine – Healing Journey of Cancer) - Selvia Arokiya Mary Amalanathan (Emerging Trends in Disease and Health Research Vol. 2, 2022)
Introduction: Worldwide, breast cancer comprises 10.4% of all cancer incidence among women. In 2004, breast cancer caused 519,000 deaths worldwide (7% of cancer deaths; almost 1% of all deaths). Many women who undergo breast surgery suffer from ill-defined pain syndromes. Statement of the Problem: A study to assess the effectiveness of twin therapeutic approaches on certain biophysiological parameters in breast cancer patients after breast surgery at selected hospital, Chennai. Objectives: This study is to: Assess the level of certain biophysiological parameters in women after mastectomy. Assess the effectiveness of twin therapeutic approaches on certain biophysiological parameters in women after mastectomy Correlate the practice of twin therapeutic approaches with certain biophysiological parameters . Associate the selected demographic variables with certain biophysiological parameters in women after mastectomy Research Design and Methods: Pre experimental research design was used. Fifty women were selected by using convenient sampling technique at government general hospital, Chennai. Results: The Level of pain shows, in the study group 49(98%) of them had moderate in the pre test and after the intervention all of them had mild pain in the post test. In relation to level of shoulder function before the intervention shows that in the study group 49(98%) of them had movement towards gravity and after intervention 24 (48%) of them had movement against gravity maximum resistance . There was a significant reduction in pain and shoulder stiffness level at a ‘P’ level of <0.001. There was a negative correlation between the pranayama practice and the level of pain, there was a positive correlation between the arm exercise practice and the level of shoulder function. There was no significant association between demographic and clinical variables with the level of pain and shoulder function in the study. Hypothesis: There is a significant difference in level of pain and shoulder function among women following breast surgery who receive pranayama & arm exercise programme. The pranayama had effect in terms of reduction of pain, arm exercise programme had effect in prevention of arm stiffness among post operative women following breast surgery. Thus the stated hypothesis was accepted. Conclusion: On the basis of the findings of the present study there was Advancing age related to increasing risk of breast cancer, level of pain also the type of surgery was associated with level of pain and shoulder function, There fore it is to be concluded that the study participants may get benefited by practice of pranayama and arm exercise program.